2006
DOI: 10.1002/erv.688
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge of health care professionals working in the eating disorders

Abstract: Background: Clinicians working in the eating disorders require a good working knowledge of basic nutrition. As different professional groups are trained in this knowledge to different degrees, it is not possible to assume that all clinicians working with the eating disorders have an equivalent knowledge base. The aim of this study is to determine the nutritional knowledge of different groups of professionals working with the eating disorders. Method: The participants were 65 clinicians (dietitians, nurses, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Nutrition counselling is an integral part of the treatment of EDs, and it is the responsibility of all HPs to be able to identify a client's inaccurate knowledge, provide accurate information and recognise when to refer to a dietitian 15 . To our knowledge, this is the first study to compare different HPs, ED patients and healthy controls on their knowledge of multiple areas of nutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition counselling is an integral part of the treatment of EDs, and it is the responsibility of all HPs to be able to identify a client's inaccurate knowledge, provide accurate information and recognise when to refer to a dietitian 15 . To our knowledge, this is the first study to compare different HPs, ED patients and healthy controls on their knowledge of multiple areas of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, minimal research has been undertaken into the level of nutrition knowledge of HPs who treat patients with EDs, a field where one would expect greater nutrition knowledge among HPs. We have identified only one study that investigated HPs who work in the ED field, by Cordery and Waller 15 . This study found that dietitians had the greatest nutrition knowledge, and nurses and psychologists did not have greater knowledge than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Question items were created based on existing literature related to RDs' eating disorder-related knowledge, beliefs, and practices. [6][7][8]12,13 However, these sources were limited. In addition, 5 items to determine perceived self-efficacy related to providing eating disorder counseling were included, such as, "I am confi-dent in counseling individuals with eating disorders."…”
Section: Methodsmentioning
confidence: 99%
“…Dietitians should be the provider of nutrition intervention in eating disorders because medical nutrition therapy is the core skill of the dietitian, it is the role that we are qualified for (ADA, 2006), and dietitians are able to provide the most accurate information to clients (Williams & O'Connor, 2000;Cordery & Waller, 2006). As stated by Cordery, the role of the dietitian therefore extends further than advising the patient because it is necessary also to educate other clinicians (Cordery & Waller, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A study examining nutrition knowledge of 65 clinicians working with eating disorder patients demonstrated that dietitians have the best nutritional knowledge of the clinician groups, and there was a poor level of nutritional knowledge in nondietitian healthcare professionals working with eating disorder patients, even though nutrition is central to the pathology and treatment of this disorder (Cordery & Waller, 2006). They recommend that therapists have sufficient basic nutritional knowledge to be able to identify distortions in their patients and therefore effectively provide nutritional intervention (Cordery & Waller, 2006). The involvement of a dietitian, within a multidisciplinary framework, is of great benefit in the treatment of eating disorders (Kirk, 1993).…”
Section: Introductionmentioning
confidence: 99%